Feasible D1–A–D2–A Random Copolymers for Simultaneous High‐Performance Fullerene and Nonfullerene Solar Cells. Issue 7 (16th November 2017) - Jeong, Mingyu; Chen, Shanshan; Lee, Sang Myeon; Wang, Zhiwei; Yang, Yankang; Zhang, Zhi‐Guo; Zhang, Chunfeng; Xiao, Min; Li, Yongfang; Yang, Changduk
Abstract: A series of PBDB‐TT n random donor copolymers is synthesized, consisting of an electron‐deficient benzo[1, 2‐ c :4, 5‐ c ′]dithiophene‐4, 8‐dione (BDD) unit and different ratios of two electron‐rich benzo[1, 2‐b:4, 5‐ b ′]dithiophene (BDT) and thieno[3, 2‐ b ]thiophene (TT) units, with intention to modulate the intrachain and/or interchain interactions and ultimately bulk‐heterojunction morphology evolution. A comparative study using 4 × 2 polymer solar cell (PSC) performance maps and each of the [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC71 BM) and the fused‐aromatic‐ring‐based molecule ( m ‐ITIC) acceptors are carried out. Given the similarities in their absorption ranges and energy levels, the PBDB‐TT n copolymers clearly reveal a change in the absorption coefficients upon optimization of the BDT to TT ratio in the backbone. Among the given acceptor combination sets, superior performances are observed in the case of PBDB‐TT5 blended with PC71 BM (8.34 ± 0.10%) or m ‐ITIC (11.10 ± 0.08%), and the dominant factors causing power conversion efficiency differences in them are found to be distinctly different. For example, the performances of PC71 BM‐based PSCs are governed by size and population of face‐on crystallites, while intermixed morphology without the formation of large phase‐separated aggregates is the key factor for achieving high‐performance m ‐ITIC‐based PSCs. This study presents a new sketch of structure–morphology–performance relationships for fullerene‐ versus nonfullerene‐based PSCs. Abstract : BDD‐based four copolymers PBDD‐TT n which contained BDT, TT, and BDD are synthesized and operated with two acceptors, PC71 BM and m ‐ITIC. Two systems have different operating mechanisms, and simultaneously high‐performances 8.44% for PC71 BM and 11.18% for m ‐ITIC are obtained.